The Dynamics of Sexuality in Joyce Carol Oates' “Where Are You Going, Where Have You Been?”: A Social Identity Perspective - Regmi, Dipendra Raj (The Outlook: Journal of English Studies, 2025)
Joyce Carol Oates (b.1938) sets her story, “Where Are You Going, Where Have You Been?” (1966), in the post-war American social context. Americans raised their voices for fundamental rights during the 1960s. Identity and sexuality became the primary concerns for many teenagers in the United States. Connie, the teenage protagonist, felt alienated from her family, and her fractured relationships with family members shaped her identity. Similarly, her willingness to ride with Arnold Friend jeopardized her sexuality. Thus, this paper examined the complications faced by teenagers in Oates’s story through the lens of social identity theory, drawing primarily on ideas from Henry Tajfel and John C. Turner. For Tajfel and Turner, socio-cultural movements, social context, and environment formed the basis for identity formation. Connie experienced the reverberations of 1960s American society and realized that her identity and sexuality were in deep crisis. The lack of an organized social environment gave rise to a communication gap, low self-esteem, and loneliness in Oates' story. The relevance of this paper lies in offering ideas to address the tension between teenagers and parents in modern families. This is how the process of resolving begins in the unsung family narratives by Oates.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">